The effects of participation in rhythmic sport on the self-esteem of adolescent girls from a disadvantaged community - Alexander, Leonieke Franziska (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Mbk.) -- University of Stellenbosch, 1998.